Antibacterial activity of ethanolic jambu batu (Psidium guajava Linn.) leaves extract against vegetative cells of Bacillus spp. - Murugan, Kalidass; Md Padzil, Khairul Naim; Sulaiman, Rabiha; Rukayadi, Yaya (Universiti Sains Malaysia, 2024)
Aims: Jambu batu (Psidium guajava Linn.) is a phytotherapic plant used in folk medicine that has active components to treat various diseases. An earlier study has reported on the analysis of its pharmacological properties and was found to possess antibacterial, antifungal, anti-inflammatory and antioxidant activity. The present study aimed to determine the antibacterial activities of P. guajava Linn. leaves extracts on the vegetative cells of Bacillus cereus ATCC33019, Bacillus megaterium ATCC14581, Bacillus pumilus ATCC14884 and Bacillus subtilis ATCC6633 and to evaluate its effects of different temperatures and pHs on antibacterial activity. Methodology and results: The susceptibility test used to determine the bacterial growth inhibition were well diffusion assay (WDA), minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC) and time-kill curve assay. The effects of various parameters on temperatures at 10 °C, 28 °C, 30 °C, 50 °C and 80 °C and pH at 3.0, 5.0, 6.7, 7.0 and 11.0 were investigated. WDA assay of the extracts resulted in 13.75 ± 0.95 and 16.25 ± 0.95 mm of inhibition zone on B. subtilis and B. cereus, respectively. The extracts can inhibit the growth with MICs value range of 0.195 to 0.781 mg/mL for B. megaterium and B. pumilus, respectively, and can kill all tested Bacillus spp. with MBCs values of 0.781 mg/mL. The killing time analyses showed that Bacillus spp. can be killed completely within 4 h at 4× MIC (0.781 to 3.124 mg/mL). The extracts remained stable under a wide range of temperatures and pHs, as there was no significant difference in the MIC and MBC values. Conclusion, significance and impact of study: Psidium guajava Linn. ethanolic leaves extract yielded good antibacterial activities, suggesting that the extract can be utilised or explored as a potential anti-Bacillus agent in food applications.